EFEKTIFITAS KOMUNIKASI INTERPERSONAL LURAH DALAM MENINGKATKAN KUALITAS KINERJA PEGAWAI PADA KANTOR LURAH TOMAGOBA - Alfin Rizaldi (JISOS: JURNAL ILMU SOSIAL, 2023)
The Effectiveness of Lurah Interpersonal Communication in Improving the Quality of Performance of Tomagoba Village Office Employees, Tidore District, Tidore City Islands. (Under the Guidance of: Mr. Abdul Kadir Ali, S.Sos.M.Si Supervisor I and Mrs. Nursakina Husen, Spd., M.Pd Advisor II). In general, this study aims to find out, The efectiveness of the Village Head's Interpersonal Communication in Improving the Quality of Employee Performance in the Tomagoba Village Office, Tidore District, Tidore Islands City and the Inhibiting and Supporting Factors for Communication Effectiveness interpersonal lurah in improving the quality of employee performance. The type of research used is descriptive qualitative by means of field observations, interviews with informants, and documentation. While the data analysis technique used, data collection, data reduction, data presentation and conclusion. The results showed that the effectiveness of interpersonal communication among employees of the Tomagoba sub-district office was in accordance with the effectiveness of interpersonal communication consisting of openness, empathy, supportive attitude, positive attitude and openness attitude. And the effectiveness of communication can be seen from the performance of employees who influence discipline and work motivation